PERSEPSI MASYARAKAT TENTANG NILAI MORAL DALAM ADAT BASIACUANG DI DESA KUMANTAN KECAMATAN BANGKINANG KABUPATEN KAMPAR - Iqbal, Ahmad; Hambali, Hambali; Gimin, Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is based on customary basiacuang in kampar regency as a custom which become the culture of kampar residents especially kumantan village. So the writer take title research "Public Perception About Moral Value In There Basiacuang I n Kumantan Village Bangkinang Sub District Kampar Regency". The formulation of the problem in this research is How Public Perceptions About Moral Value In There Basiacuang In Kumantan Village Sub District Bangkinang Kampar District? The purpose of this study is to Public Perceptions About Moral Value In There Basiacuang In Kumantan Village Sub-District Bangkinang Kampar District. The population of this study is the community of kumantan village which amounted to 5,119 people and the sample amounted to 50 people. The instrument of data collection is questionnaire consists of 27 questions. The interview consisted of 8 questions. In analyzing the data using Qualitative Descriptive analysis. The results of this study show that the Public Perceptions About Moral Value In There Basiacuang In Kumantan Village Sub-District Bangkinang Kampar District seen from the percentage of 50respondents stated 10.07% for the category is not good, 21.93% for the less good category , 55.19% for good category, and 12.81% for very good category.Keywords:Perception, CustomBasiacuang